MARKETPLACE APPLICATION FOR HYDROPONIC AGRICULTURAL PRODUCTS - Usman Nurhasan (International Conference on Industrial Revolution for Polytechnic Education, 2020)
In the industrial era 4.0, the agricultural sector began to shift to the concept of modern agriculture that embraces sustainable agriculture. The concept of sustainable agriculture is to pay attention to human needs in the future. Many ways can be applied in the development of sustainable agriculture, one of which is hydroponic farming. However, at present, hydroponic plants are not widely known to the public due to the lack of promotion media for hydroponic farmers, resulting in the absence of a buying and selling process for hydroponic vegetables. One of the efforts is to develop a hydroponic e-marketplace based education system. The hydroponic e-marketplace-based trading system can be used as an alternative for hydroponic farmers, as a media for promotion, communication and information. The benefits felt by hydroponic farmers and consumers directly and indirectly have a positive influence, especially from the increasingly broad marketing channels can increase production demand, make it easier for consumers to shop for hydroponic vegetables by saving time and energy, and makes it easier for consumers to see the market price of hydroponic vegetables for sale.